PENGARUH PERTUMBUHAN EKONOMI DAN PENGANGGURAN TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI PROVINSI SUMATERA SELATAN PERIODE TAHUN 2004 – 2018 - Novegya Ratih Primandari (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2020)
This study aims to determine the effect of economic growth and unemployment on the Human Development Index (HDI) in South Sumatra Province in the period 2004 - 2018. The analytical tool used is multiple linear regression in which economic growth and unemployment as independent variables and the index of human development as the dependent variable . The data used are time series data from 2004 - 2018 sourced from BPS. Based on multiple linear regression analysis results show that growth and unemployment have a positive effect on the human development index both partially and simultaneously. As for the contribution of the effect of economic growth and unemployment on the human development index the results were 45.3% and the remaining 54.7% were influenced by other variables such as poverty, education level and health level.